ISFET pH Sensor Characterization: Towards Biosensor Microchip Application. - Abdul Rani, Rozina; Sidek, Othman (2004)

(untitled)
The ion-sensitive field effect transistor (ISFET) based pH sensor has the advantages of smaller size, fast response time and fabrication compatible with standard MOS technology.